RETRACTED: Analysis of dependences for hydraulic calculation of pipes made of polymer materials - Terekhov L.D.; Smolinl E.S. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001